Design and implement of robotic arm and control of moving via IoT with Arduino ESP32 - Ahmed, Anwer Sabah; Marzog, Heyam A.; Abdul-Rahaim, Laith Ali (International Journal of Electrical and Computer Engineering (IJECE), 2021)
Every day, the technologies are expanding and developed with extra things to them. A cloud computing (CC) and Internet of things (IoT) became deeply associated with technologies of the internet of future with one supply the other a way helping it for the successful. Arduino microcontroller is used to design robotic arm to pick and place the objects by the web page commands that can be used in many industrials. It can pick and place an object from source to destination and drive the screws in into its position safely. The robot arm is controlled using web page designed by (html) language which contain the dashboard that give the commands to move the servos in the desired angle to get the aimed direction accordingly. At the receiver end there are four servo motors which are made to be interfaced with the micro controller (Arduino) which is connected to the wireless network router. One of these is for the arm horizontally movement and two for arm knee, while the fourth is for catch tings or tight movement. Two ultra-sonic sensors are used for limiting the operation area of the robotic arm. Finally, Proteus program is used for the simulation the controlling of robot before the hardware installation